Mixed-methods evaluation of a novel online STI results service. (11th January 2018) - Gibbs, Jo; Aicken, Catherine R H; Sutcliffe, Lorna J; Gkatzidou, Voula; Tickle, Laura J; Hone, Kate; Sadiq, S Tariq; Sonnenberg, Pam; Estcourt, Claudia S
Abstract : Objectives: Evidence on optimal methods for providing STI test results is lacking. We evaluated an online results service, developed as part of an eSexual Health Clinic (eSHC). Methods: We evaluated the online results service using a mixed-methods approach within large exploratory studies of the eSHC. Participants were chlamydia- positive and negative users of online postal self-sampling services in six National Chlamydia Screening Programme (NCSP) areas and chlamydia-positive patients from two genitourinary medicine (GUM) clinics between 21 July 2014 and 13 March 2015. Participants received a discreetly worded National Health Service 'NHS no-reply' text message (SMS) informing them that their test results were ready and providing a weblink to a secure website. Participants logged in with their date of birth and mobile telephone or clinic number. Chlamydia-positive patients were offered online management. All interactions with the eSHC system were automatically logged and their timing recorded. Post-treatment, a service evaluation survey (n=152) and qualitative interviews (n=36) were conducted by telephone. Chlamydia-negative patients were offered a short online survey (n=274). Data were integrated. Results: 92% (134/146) of NCSP chlamydia-positive patients, 82% (161/197) of GUM chlamydia-positive patients and 89% (1776/1997) of NCSP chlamydia-negative participants accessed test results within 7 days. 91% of chlamydia-positive patients were happy with the results service; 64% of those who had tested previously found the results service better or much better than previous experiences. 90% of chlamydia-negative survey participants agreed they would be happy to receive results this way in the future. Interviewees described accessing results with ease and appreciated the privacy and control the two-step process gave them. Conclusion: A discreet SMS to alert users/patients that results are available, followed by provision of results via a secure website, was highly acceptable, irrespective of test result and testing history. The eSHC results service afforded users privacy and control over when they viewed results without compromising access.